A comparison of base running start techniques in collegiate fastpitch softball athletes - Massey, K. P.; Miller Brouillette, K.; Martino, M. (Journal of Human Sport & Exercise, 2018)
This study examined the time difference between three different base running start techniques. Thirteen Division II collegiate softball players performed maximal sprints off a softball bag at two different distances. Sprint times at 4.57 and 18.29 meters for each technique were measured using Fusion Sport`s Smartspeed System. At both 4.57 and 18.29 meters, the rocking start (0.84 ± 0.10; 3.04 ± 0.16 s) was found to be significantly faster (in seconds) than both the split technique (1.01 ± 0.04; 3.27 ± 0.12 s) and the crouch technique (1.05 ± 0.12; 3.35 ± 0.16 s) (p < 0.05). Results recommend that the rocking start technique be implemented as the starting position off the bag in fastpitch softball. Implementing the rocking technique may enhance performance and success in stealing and base running.